A transparent, glue-free, skin-attachable graphene pressure sensor with micropillars for skin-elasticity measurement. (29th May 2019) - Chun, Sungwoo; Kim, Da Wan; Kim, Jiwon; Pang, Changhyun
Abstract: Strong peeling resistance and water-drainable properties on rough and wet skin surfaces are highly desirable for realizing wearable and skin-attachable electronic sensors. Here, we propose a transparent, sensitive, glue-free pressure sensor for skin electronics. To achieve a thin, light-weight, transparent, and stretchable sensor patch, we laminated a single-layer graphene film as a sensing element on a thin polymeric supporter of polydimethylsiloxane. By assembling the graphene layer with densely populated micropillars, the pressure sensor achieved 10 times the sensitivity of a similar sensor without micropillars in the low-pressure range (<6 kPa). We then employed hexagonal patterns inspired by the toe pads of a tree frog, giving the assembled patch sensor with strong peeling resistance under both dry and wet conditions on surfaces such as silicon (15.5 J cm −2 for dry and 11.6 J cm −2 for wet conditions) and pig skin (2.0 J cm −2 for dry and 1.4 J cm −2 for wet conditions) without contamination after detachment. Our layered sensor patch also demonstrated successful measurement of water-dependent skin elasticity with transparent, conformal, and residual-free attachment, suggesting a variety of cosmetic and medical applications.